Girish Kasaravalli’s Three Women : Reflecting Women’s Suffering, Redefining Cultural Spaces - Dr. Poarkodi.N, Dr. Hepzibah Beulah Suganthi T.R. (South Eastern European Journal of Public Health, 2025)
Drawing inspiration from Italian neo-realism and the Navya literary movement, Filmmaker Girish Kasaravalli has made remarkable contribution to the Indian New Wave Cinema, both in thematic concerns and aesthetic sensibility. Girish’s work bear ample testimony to his indomitable spirit of experimentation with the film form and content. Further, Girish’s works have women-centric narratives that expose the negative shades of patriarchal system. This paper will explore the characterisation of three of his women protagonists from films - Thayi Saheba, Hasina and Gulabi Talkies, and their struggles against patriarchal order.